ANALISIS PENJADWALAN TENAGA KERJA DENGAN MENGGUNAKAN METODE TIBREWALA, PHILIPPE DAN BROWNE PADA PT. JAPFA COMFEED INDONESIA TBK. UNIT MAKASSAR - Nadzirah Ika Sari; Andi Pawennari; Nurul Fatimah (Journal of Industrial Engineering Management, 2019)
Labor scheduling is the allocation of human resources to the work stations according to the needs. To increase productivity the company must schedule the labor optimally. PT. Japfa Comfeed Indonesia Tbk. Makassar Unit is one of company that produces the animal feed with a capacity of 4 tons in a day that located on Jalan Ir. Sutami KM 17 PO BOX Makassar. In workers allocating, the company implements labor scheduling with 3 work shifts and 1 day off in 1 week in the production section. Human resources are very important to notice. Therefore, to increase the productivity of the company so it's need for additional day off for each part of the labor production. To accommodate 3 work shifts in a day and 2 days off in 1 week, this research used a modified of tibrewala, philippe and browne algorithm method. Modification of this algorithm changes and adds from 3 steps to 5 steps and changes the tabular table format for scheduling workers for three shifts. Labor Scheduling with 5 working days and 2 days off needs of 20 people of labor in the hand add process, 36 people in the bagging process, 7 people in the panel process and 7 people in the press process. The excess of labor that occurred was 9 man days (equivalent to 5.6 people) in the hand add process, 36 man days (equivalent to 7.2 people in the bagging process, 17 man-days (equivalent to 3.4 people) on the panel process and 17 man-days (equivalent to 3.4 people) in the press process. The excess of the labor can be utilized when the labor is not going to work because of illness, permission or leave. This scheduling is expected to be able to keep the health and safety of the labor so that it can be optimal to work to increase the productivity of the company.